Identification of valued users to generate more telecom filigence - Khan, N.; Shah, Asadullah; Nusratullah, Kajal (University of Sindh, 2018)
Stay connected is a well-known advantage of telecommunications. Telecom diligence have introduced an easy and enormous way to people to keep in touch. From the last decades, a remarkable growth is noted in telecommunication industry. The number of telecom users has enormously increased. With increasing demands, it is becoming challenges for CSPs (Communication Service Providers) to provide best services. In order to provide finest services a very important step is to monitor the activities of subscribers on the network. Call detail records (CDRs) can play a vital role in monitoring process. CDRs provide a diversity of information about the subscribers. Even though Call Detail Records were initially gathered and stored for billing purpose, but the huge amount of digital data is generated by calling, texting and internet usage etc., generates events, sate and errors that provide useful insights. These digital footprints can be analysed to produce worthy information like network optimization, user's patterns and behavior identification, valued users identification, suspects and their connected association and much more. This paper has identified an important use of call detail records to discover and analyze the networks generating more income for offering new services and promotions to those valued users's networks.